PENGARUH MODAL USAHA, JAM USAHA DAN TEKNOLOGI TERHADAP PRODUKTIVITAS DAN PENDAPATAN PEDAGANG PASAR BADUNG, KOTA DENPASAR SAAT PANDEMI COVID- 19 - Wulan Diantari, Anak Agung Istri; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
This research aims to analyze the influence of business capital, business hours and technology on the productivity and income of Badung Market traders during the Covid-19 pandemic . The data used in this study is primary data obtained through questionnaires or directly to respondents. This study uses a probability sampling method of determining the sample, where the number of samples is 100 traders. The data analysis technique used is path analysis. The results show that Business Capital and Business Hours have a positive and significant effect on the productivity of Badung Market traders during the pandemic, while Business Capital and productivity have a positive and significant impact on the income of Badung Market traders, and the technology variable has no significant effect on the productivity and income of traders because traders there are still many badung markets who do not understand and lack of facilities in using technology as a promotional medium, therefore technology has no effect. Productivity mediates the effect of capital on income, but productivity does not mediate the effect of hours of work and technology on income .